Emotional Burnout and Mental Health Predictors Among Female Preschool Teachers - Ekawati Ekawati; Yuliani Setyaningsih; Ida Wahyuni; Bina Kurniawan (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Preschool teacher profession with the work demands of preschool female teachers with diverse characters is a challenge and a source of pressure that can lead to poor mental health and job burnout. This study was conducted to analyse factors associated with mental health and subjective job burnout. Methods: A cross-sectional study involving 37 female early childhood teachers in Semarang. Data were collected using a structured Google Form-based questionnaire containing questions regarding work capacity, such as age, weight, height, tenure, and marital status and analysed with descriptive statistics and chi-square test. Results: Most preschool female teachers experienced mental health 59.5% and subjective job burnout 37.8%. The results of the relationship test explained that there was a relationship between tenure and mental health (p=0.013). Conclusion: We showed that tenure of preschool female teachers is significantly associated with mental health. The provision of mental health management and fatigue prevention education are needed for both new and experienced teachers.